Pengembangan Model Blended Learning Matematika Terapan Untuk Meningkatkan Kemampuan Komunikasi dan Pemecahan Masalah Bagi Mahasiswa Politeknik Negeri Bali - I Ketut Darma; I Gede Made Karma; I Made Anom Santiana; Irene E (Politeknik Negeri Bali, 2020)
The purpose of the research is to describe the need for developing teaching materials in the form of textbooks and student activity sheets (SAS) based on applied mathematics, and 2) get a draft of textbooks and LKM, applied mathematics based on blended learning. Its development uses the Thiagarajan 4-D model. At present the define, design and part of the develop stage are being carried out. Implementation in the field of engineering of the Bali State Polytechnic. Data were collected using survey methods, documents and questionnaires and analyzed using descriptive statistics. The results of the analysis found that there were 13 mathematics learning achievements and 51 sub-achievements. Student characteristics: 1) attitude toward mathematics is very positive, interest in learning is moderate, 2) motivation for learning is high; 4) high learning independence, 5) 79.7% had difficulty understanding sub textbooks given by lecturers, 6) 89.6% needed alternative teaching materials to understand mathematical concepts, and 7) 83.3% agreed to develop mathematical teaching materials Applied blended learning based uses a problem solving approach. The draft of applied mathematics teaching materials based on blended learning, the material was developed referring to learning achievements, achievement of learning subjects, and sub-achievement of mathematics learning. The main material includes, namely: 1) algebra, 2) geometry; 3) trigonometry; and 4) calculus. The material order, arranged with a hierarchical approach. The four materials are packaged into 2 textbooks and LKM. The teaching material is integrated in the LMS Schoology model. The results of the validator of the draft teaching materials show that teaching materials by making minor revisions, are worth using as materials only